Computational Insights Into the Inhibition Mechanism of Proanthocyanidin B2 on Tau Hexapeptide (PHF6) Oligomer - Li, Qin; Xiong, Chunmei; Liu, Hongli; Ge, Huizhen; Yao, Xiaojun; Liu, Huanxiang (Frontiers in Chemistry, 2021)
The formation of amyloid fibrils from Tau is a key pathogenic feature of Alzheimer’s disease (AD). To disturb the formation of Tau aggregates is considered as a promising therapeutic strategy for AD. Recently, a natural product proanthocyanidin B2 (PB2) was confirmed to not only inhibit Tau aggregation, but also disaggregate Tau fibrils. Herein, to explore the inhibition mechanism of PB2 against Tau fibril and to provide the useful information for drug design and discovery, all-atom molecular dynamics simulations were carried out for the ordered Tau hexapeptide PHF6 oligomer in the presence and absence of PB2. The obtained result shows that PB2 can transform PHF6 oligomer from the ordered β-sheet structure into disordered one. Moreover, the clustering analysis and binding free energy calculations identify that S3 site is the most potential binding site. At S3 site, by hydrophobic and hydrogen bond interactions, the residues V309, Y310 and K311 are essential for binding with PB2, especially K311. In a word, our study reveals the molecular mechanism of PB2 inhibiting PHF6 aggregation and it will provide some valuable information for the development of Tau aggregation inhibitors.